Interface of drug use - Ludescher, N. O.; Vergilio, R. R.; Lucio, C. C. [UNESP]; Santos, J. E. G. [UNESP] (IOS Press, 2012)
Packaging and labeling play a crucial role awhile protecting medicaments and transmitting a range of crucial information to the users. Taking into account the scarcity of specific studies in this area, it was considered great the need for a comprehensive survey about customers' satisfaction when handling these containers.
Keywords: Packaging; drug; handling; ergonomics; usability